Estimation of genetic variability, correlation and path analysis in elite rice genotypes (Oryza sativa L.) - Kumari, Shikha; Sinha, Sima; Satyendra; Kumar, Vivek; Singh, Ravi Shankar; Kumar, Anand; Kumar, Ravi Ranjan; Singh, SN (ORYZA-An International Journal of Rice, 2023)
A trial was carried out to explore the variability and correlation among thirty five rice (Oryza sativa L.) germplasm for fifteen characters, during kharif 2017-18 at Bihar Agricultural University, Sabour, (Bihar). Analysis of variance revealed significant differences among all the genotypes and for all fifteen characters, which reflects that considerable amount of variability, were present in the genotypes. Two genotypes LPD104-B-B-1-8-2-1-1and RP5124-11-6-2 were identified as the superior genotypes for yield. The highest magnitude of genotypic coefficient of variation was recorded for length breadth ratio of rice grain, however highest phenotypic coefficients of variation were recorded for grain yield per plant followed by kernel length. High heritability coupled with high genetic advance as per cent mean was observed for kernel length and length breadth ratio. In this experiment grain yield per plant had positive and significant association with biological yield per plant, days to 50 per cent flowering, days to maturity, while remaining characters had non-significant association with yield. Path coefficient analysis revealed that the biological yield per plant, harvest index and kernel length had high positive direct effects on grain yield per plant indicating true relationship of these characters with grain yield. Therefore, these traits could be considered in rice improvement programme.